2023
DOI: 10.1002/pri.2062
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of neuromuscular electrical stimulation training combined with exercise on patient‐reported outcomes measures in people with knee osteoarthritis: A systematic review and meta‐analysis

Maurício Tatsch Ximenes Carvalho,
Victor Hugo Guesser Pinheiro,
Cristine Lima Alberton

Abstract: ObjectiveThis study examined the effectiveness of neuromuscular electrical stimulation (NMES) added to the exercise or superimposed on voluntary contractions on patient‐reported outcomes measures (PROMs) in people with knee osteoarthritis (OA).MethodsThis systematic review was described according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Randomized controlled trials (RCTs) were obtained from a systematic literature search in five electronic databases (PubMed, PEDro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…All other studies that have investigated the effect of EMSmostly the term neuromuscular electrical stimulation (NMES) is used in literaturein knee OA have only used a local stimulation. The results of two recent meta-analysis on the effect of local EMS in individuals with knee OA indicate an increase in quadriceps muscle strength [52], but no significant reduction in pain [21,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All other studies that have investigated the effect of EMSmostly the term neuromuscular electrical stimulation (NMES) is used in literaturein knee OA have only used a local stimulation. The results of two recent meta-analysis on the effect of local EMS in individuals with knee OA indicate an increase in quadriceps muscle strength [52], but no significant reduction in pain [21,52].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by de Oliveira et al [20] showed moderate evidence in favour of neuromuscular electrical stimulation (NMES) alone or in combination with exercise for isometric quadriceps strengthening. A recent meta-analysis by Carvalho et al [21] reported insufficient evidence on the effects of NMES combined with exercise compared to exercise alone on patient-reported outcomes (e.g. pain).…”
Section: Introductionmentioning
confidence: 99%